Vancomycin Capped with Silver Nanoparticles as an Antibacterial Agent against Multi-Drug Resistance Bacteria - Mahsa Esmaeillou; Gholamreza Zarrini; Mohammad Ahangarzadeh Rezaee; Javid Shahbazi mojarrad; Ali Bahadori (Tabriz University of Medical Sciences, 2017)
Purpose: Many antimicrobial medications are available to combat infections. However, the indiscriminate use of antibiotics has produced antibiotic resistance in the case of many bacterial pathogens. This study focuses on the development of nanoparticles (NPs) that enhance the in vitro antibiotic activity of vancomycin against multi-drug resistant (MDR) organisms. Methods: Spherical shaped thioglycolic acid-stabilized silver nanoparticles (TGA-AgNPs) were prepared by using a simple chemical reduction method. Then, vancomycin was conjugated to the terminal carboxyl of TGA in the presence of N-Hydroxysuccinimide (NHS) and N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride (EDC). Afterwards, the antibacterial activity of these nanoconjugates was examined by using the minimum inhibitory concentration (MIC) assay against MDR bacteria. Results: The rate of vancomycin bound to the AgNPs was 19.6%. The MIC values of vancomycin (Van)-capped AgNPs against tested pathogens were in the range of (3.2, 1.6, 0.8, 0.4, 0.2, 0.1, 0.05, and 0.025 µl/ml). The MIC was 0.1 µg/ml for VRE, MIC≤0.02 µg/ml for MRSE, and 0.05 µg/ml for S. aureus. The MIC corresponded to the MBC for all bacterial species. Conclusion: This study indicated that some antimicrobial agents like vancomycin can be conjugated with AgNPs. This can lead to increased antimicrobial activity against MDR microorganisms.